Odpowiedzi

2010-04-12T15:37:41+02:00
A)6x-5=2x+15
6x-2x=15+5
4x=20/:4
x=5

b)7x+1=5-2x
7x+2x=5-1
9x=4/:9
x=4/9

c)-(x-1)=2(1+x)
-x+1=2+2x
1-2=2x+x
-1=3x/:3
-1/3=x

d)9(x-2)=0
9x-18=0
9x=0+18
9x=18/:9
x=2



1 5 1
2010-04-12T15:41:27+02:00
A) 6x-5=2x+15
6x-2x=15+5
4x=20 /:4
x=5

b)7x+1=5-2x
7x+2x=5-1
9x=4 /:9
x=4/9

c)-(x-1)=2(1+x)
-x-2x=2-1
-3x=1 /-3
x=-(1/3)

d)9(x-2)=0
9x=18/:9
x=2
1 4 1
2010-04-12T15:42:04+02:00
A) 6x-5=2x+15
6x-2x=5+15
4x=20 /4
x=5

b)7x+1=5-2x
7x+2x=5-1
9x=4 /9
x=4/9

c)-(x-1)=2(1+x)
-x+1=2+2x
-x-2x=2-1
-3x=1 /(-3)
x=-(1/3)

d)9(x-2)=0
9x-18=0
9x=18 /9
x=2
1 5 1